Green Solvents for the Liquid Phase Exfoliation Production of Graphene: The Promising Case of Cyrene - Fernandes, João; Nemala, Siva Sankar; De Bellis, Giovanni; Capasso, Andrea (Frontiers in Chemistry, 2022)
The liquid phase exfoliation (LPE) of graphite has allowed to produce graphene materials on a large scale and at a reasonable cost. By this method, stable dispersions, inks and liquid suspensions containing atomic-thick graphene flakes with tailored concentrations can be produced, opening up applications in a wide range of cutting-edge technologies, such as functional coatings, printed and flexible electronics, and composites. However, currently established LPE techniques raise several health and environmental risks, since unsafe and toxic solvents (such as NMP, DMF, and DMSO) are predominantly employed. It appears necessary to unlock eco-friendly and sustainable methods for the production of graphene at an industrial scale. This review focuses on the latest developments on the use of “green” solvents for the LPE production of graphene. Among them, the bio-based solvent Cyrene is singled out and analyzed in detail, comparing its performance in terms of processing and applications to those of conventional LPE solvents.